Preparation method of catalyst for preparing low-carbon olefin from synthesis gas through one-step method
Through a new catalyst preparation method, Fe2O3-CoO catalyst is prepared using materials such as ferric nitrate and oxalic acid, and combined with modifiers and molecular sieves, the problems of low-carbon olefins are solved in the prior art. Achieve efficient and low-cost low-carbon olefin preparation.
Patent Information
- Application Number
- CN202310956709.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-01
AI Technical Summary
The existing low-carbon olefin technology for indirect synthesis gas has problems such as complex reaction steps, large energy consumption and low selectivity, resulting in high production efficiency and cost of low-carbon olefins.
A catalyst preparation method for preparing low-carbon olefins by using a one-step syngas method. Fe2O3 is obtained by grinding, drying and calcining iron nitrate and oxalic acid, then mixed with CoO, adding modifiers and molecular sieve, and then centrifugation, drying and tableting. Then make the catalyst.
The prepared catalyst has high activity, high selectivity and good stability, and can efficiently prepare low-carbon olefins in a one-step synthesis gas process to reduce energy consumption and cost.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysis, and in particular relates to a method for preparing a catalyst for preparing low-carbon olefins by a one-step process of synthesis gas. Background Art
[0002] Low-carbon olefins (especially ethylene, propylene, butene, etc.) are the most basic and important organic chemical raw materials. Traditional production processes are heavily dependent on petroleum. According to my country's resource conditions of "relatively rich in coal, lacking in oil, and little gas", using "coal" instead of "oil" to produce low-carbon olefins is one of the important ways to achieve clean and efficient utilization of my country's coal and ensure national energy security. The development of coal-based synthesis gas to produce low-carbon olefin technology has important strategic significance and practical application value.
[0003] The indirect process of producing low-carbon olefins from syngas includes two steps. At present, the indirect process of producing low-carbon olefins is relatively mature, such as the MTO process developed by UOP in the United States and the new DMTO process developed by the Dalian Institute of Chemical Physics of the Chinese Academy of Sciences. However, the reaction steps of the indirect process are relatively complicated, which will bring huge energy consumption and additional costs. Compared with the indirect process, the one-step process of producing low-carbon olefins has attracted more and more attention due to its advantages such as low energy consumption, low cost and short process.
[0004] At present, there are mainly the following catalytic systems for preparing light olefins from synthesis gas: (1) Improved FT catalyst Dent et al. found that cobalt-based catalysts can be used for highly selective synthesis of light olefins, such as CoCu / Al2O3, Fe-Co / C, Co-Fe / SiO2, Co-Ni / MnO2, Fe-Co alloy and other systems. Among them, the improved FT catalyst developed by Ruhr Chemie Company has better results. By adding Mn or Ti and other components to the Fe-ZnO-K2O catalyst and adopting high-speed gas circulation, the CO conversion rate reached 80% and the light olefin selectivity reached 70%; (2) Ultrafine particle catalyst Venter et al. obtained a highly dispersed K-FeMn catalyst supported on activated carbon by the carbonyl complex decomposition method. The catalyst has high activity, and C2-C4 olefins account for 85-90% of the product. Methane is the only other product detected. Cupta et al. used laser pyrolysis to prepare catalytically active FexSiyCz powder, with a CO conversion rate of 40%, a C2-C4 selectivity of 87%, and only a small amount of methane. Zhong Bing and others from Shanxi Coal Chemical Research Institute successfully developed a new ultrafine particle Fe / Mn catalyst with practical background by using the degradation method of organic salt complexes. The CO conversion rate is greater than 95%, and the C2-C4 olefins in the product are greater than 80%. Zhang Jingchang from Beijing University of Chemical Technology used laser pyrolysis to prepare highly dispersed amorphous ultrafine iron powder and carbon powder, and successfully prepared a new active species Fe3C for FT synthesis through solid phase reaction. Nanocatalysts such as Fe-C, Fe-C-Mn-K, and Fe-CMn with Fe3C as the main body were prepared, with a CO conversion rate of 90% and an olefin selectivity of more than 80%; (3) Amorphous synthesis catalyst Yokoyama et al. used amorphous Fe 40 Ni 40 P 16 B4 compound, CO conversion rate 50%, C2-C5 hydrocarbon selectivity 65%, while the crystalline catalyst mainly produces methane; (4) Zeolite catalyst systems include Co-A, Co-Y, Fe-Y, etc. Ballivet-Tketchenko et al. prepared zeolite-supported highly dispersed iron catalysts with light olefin selectivity as high as 88-98%. In the C2-C4 range, iron catalysts supported by ZSM-5, mercerized, and 13X zeolites also show light olefin selectivity.
[0005] There are major challenges in the production of light olefins from syngas: product distribution is limited by the low yield of light olefins in FT synthesis, resulting in low overall selectivity for light olefins; due to the highly exothermic reaction, it is easy to cause local overheating and promote methanation and carbon deposition, reducing the overall olefin yield. Olefins are easily converted into saturated alkanes by secondary hydrogenation reactions as intermediate products.
[0006] Therefore, developing a catalyst for the one-step production of light olefins from synthesis gas and preparing a catalyst with high activity, high selectivity, and good stability is an important issue that researchers currently need to solve. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a catalyst for preparing light olefins from synthesis gas in one step, so as to prepare a catalyst with high activity, high selectivity and good stability.
[0008] The main technical scheme of the present invention is: a method for preparing a catalyst for preparing low-carbon olefins from synthesis gas in one step, characterized in that ferric nitrate and oxalic acid are ground, dried and calcined to obtain Fe2O3, Fe2O3 is mixed with CoO to obtain a composite active component Fe2O3-CoO, a modifier is added to obtain a modified active component Fe2O3-CoO-SiO2, the modified active component is mixed with a molecular sieve, centrifuged, dried, tableted, crushed and sieved to obtain a catalyst.
[0009] Generally, the catalyst preparation method of the present invention is prepared by the following steps: 1) Using a solid phase method, ferric nitrate and oxalic acid were ground in a mortar, dried, and calcined to prepare Fe2O3; 2) The Fe2O3 prepared in step (1) and CoO are mixed in proportion and dispersed in ethanol under ultrasonic conditions; tetraethyl silicate is added to the prepared solution under stirring, the pH is adjusted, and the solution is washed by centrifugation until it is neutral; 3) dispersing the composite active component Fe2O3-CoO prepared in step (2) in an ethanol solution under ultrasonic conditions, and adding a modifier to obtain a modified active component Fe2O3-CoO-SiO2; 4) The modified active component Fe2O3-CoO-SiO2 prepared in step (3) is mixed with the molecular sieve in proportion, ultrasonically dispersed in ethanol, centrifuged, dried, tableted, crushed, and sieved to obtain a catalyst.
[0010] Preferably, in step (1), grinding is performed for 30 to 40 minutes, drying is performed at 100 to 130°C for 12 to 15 hours, and calcination is performed at 550 to 850°C for more than 2 hours.
[0011] Preferably, in step (2), the molar ratio of Fe2O3 to CoO is 3 to 4.
[0012] Preferably, in step (2), alkali is added to adjust the pH.
[0013] More preferably, the base is one or more of ammonia water, ammonium carbonate and ammonium bicarbonate.
[0014] Preferably, in step (3), the modifier is selected from one or more of hexadecyltrimethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, vinyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
[0015] Preferably, in step (4), the molecular sieve is one or more selected from the group consisting of molecular sieves SAPO-34, SAPO-18, ZSM-5, and MCM-41.
[0016] Preferably, in step (4), the mass ratio of the modified active component to the molecular sieve is (1-2):1.
[0017] The main advantages of the present invention are: (1) Hydrophobic modification by silanization can inhibit the WGS reaction on Fe-based Fischer-Tropsch synthesis catalysts and reduce the formation of C1 by-products; (2) The Fe-based Fischer-Tropsch synthesis catalyst is combined with an acidic zeolite molecular sieve. Since its acidic center is conducive to the cracking of long-chain hydrocarbons, it can improve the selectivity of olefin products. Implementation
[0018] The present invention is described in detail below with reference to the embodiments. Example 1
[0019] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of hexadecyltrimethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 in a ratio of 1:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-1. Example 2
[0020] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate, 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution. 0.1 mL of hexadecyltrimethoxysilane was added to each gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-18 at a ratio of 1:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-2. Example 3
[0021] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of hexadecyltrimethoxysilane was added per gram of composite active group for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve MCM-41 in a ratio of 1:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-3. Example 4
[0022] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of hexadecyltrimethoxysilane was added to each gram of composite active group for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve ZSM-5 at a ratio of 1:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-4. Example 5
[0023] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of hexadecyltrimethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-5. Example 6
[0024] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of dimethyldiethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-6. Example 7
[0025] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of trimethylethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-7. Example 8
[0026] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of vinyltrimethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-8. Example 9
[0027] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 550 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 3:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonium carbonate and 20 mL of deionized water were added, and stirring was continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of γ-aminopropyltriethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-9. Example 10
[0028] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 40 min, dried in an oven at 110 ℃ for 15h to obtain ferric oxalate, and then calcined at 550 ℃ for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 4:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonia water, 20 mL of deionized water were added, and stirring continued for 4 h, centrifuged and washed to neutral, and dried at 60℃. The above-prepared catalyst was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of hexadecyltrimethoxysilane was added per gram of catalyst for modification, and stirred at 70 ℃ for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-10. Embodiment 11
[0029] 8.08g of ferric nitrate nine hydrate and 3.79g of oxalic acid two hydrate were ground in a mortar for 30 min, dried in an oven at 110 °C for 15h to obtain ferric oxalate, and then calcined at 850 °C for 2h to obtain pure Fe2O3. The prepared Fe2O3 and CoO were mixed in a ratio of 4:1, dispersed in 250 mL of ethanol under ultrasonic conditions, ultrasonicated for 20 min, and 2.5 mL of tetraethyl silicate was added under stirring, stirred for 4 h, 5 mL of ammonia water, 20 mL of deionized water were added, and stirring continued for 4 h, centrifuged and washed to neutral, and dried at 60 °C. The composite active component prepared above was dispersed in 40 mL of 75% ethanol solution, and 0.1 mL of hexadecyltrimethoxysilane was added per gram of composite active component for modification, and stirred at 70 °C for 3 h to obtain the modified active component Fe2O3-CoO-SiO2. The prepared modified active component was mixed with molecular sieve SAPO-34 at a ratio of 2:1, ultrasonically dispersed in ethanol, centrifuged, and dried. The obtained catalyst was tableted, crushed, and sieved, and marked as S-11.
[0030] Catalyst performance evaluation Take 10 ml of catalyst samples S-1 to S-11 respectively, load them into a fixed bed reactor, and heat them at a reaction temperature of 250-400°C, a pressure of 1-2.5 MPa, and a space velocity of 1000-10000 h -1 The selectivity and yield of light olefins were investigated under the conditions of n(H2) / n(CO)=1~1.5. The evaluation results are shown in Table 1.
[0031] Table 1
[0032] As shown in Table 1 above, samples S-1, S-2, S-4, and S-5 investigated the effects of catalysts prepared by mixing the modified active component Fe2O3-CoO-SiO2 with five different molecular sieves, SAPO-34, SAPO-18, MCM-41, and ZSM-5, respectively. The results showed that the olefin selectivity and yield were average, among which the catalyst prepared with molecular sieve SAPO-34 had the best effect.
[0033] Samples S-1 and S-5 investigated the use of two different ratios of modified active components and molecular sieve SAPO-34 to prepare different catalysts. The results showed that the catalytic effect was good when the mass ratio of modified active components to molecular sieve was 2:1.
[0034] Five different modifiers, including hexadecyltrimethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, vinyltrimethoxysilane, and γ-aminopropyltriethoxysilane, were added to the composite active components of samples S-5, S-6, S-7, S-8, and S-9, respectively. The results showed that the catalyst modified with the modifier hexadecyltrimethoxysilane had better catalytic effect.
[0035] Sample S-10 investigated the effect of the ratio of active components on the catalyst activity. The results showed that the catalyst effect was optimal when the molar ratio of Fe2O3 to CoO was 4:1.
[0036] Sample S-11 investigated the effect of calcination temperature on the catalyst effect, and the results showed that calcination temperature had little effect on the catalyst.
[0037] In summary, the molar ratio of Fe2O3 to CoO is 4:1, and the sample S-10 prepared by using the modifier hexadecyltrimethoxysilane and the mass ratio of the modified active component Fe2O3-CoO-SiO2 to the molecular sieve SAPO-34 is 2:1 has the best catalytic effect, with an olefin selectivity of 65.8% and a maximum yield of 40.8%.
Claims
1. A method for preparing a catalyst for preparing light olefins from synthesis gas in one step, characterized in that Ferric nitrate and oxalic acid are ground, dried and calcined to obtain Fe2O3, Fe2O3 is mixed with CoO to obtain a composite active component Fe2O3-CoO, a modifier is added to obtain a modified active component Fe2O3-CoO-SiO2, the modified active component is mixed with a molecular sieve, centrifuged, dried, tableted, crushed and sieved to obtain a catalyst.
2. The method for preparing a catalyst according to claim 1, characterized in that Prepared by the following steps: 1) Using a solid phase method, ferric nitrate and oxalic acid were ground in a mortar, dried, and calcined to prepare Fe2O3; 2) The Fe2O3 prepared in step (1) and CoO are mixed in proportion and dispersed in ethanol under ultrasonic conditions; tetraethyl silicate is added to the prepared solution under stirring, the pH is adjusted, and the solution is centrifuged and washed until neutral; 3) dispersing the composite active component Fe2O3-CoO prepared in step (2) in an ethanol solution under ultrasonic conditions, and adding a modifier to obtain a modified active component Fe2O3-CoO-SiO2; 4) The modified active component Fe2O3-CoO-SiO2 prepared in step (3) is mixed with the molecular sieve in proportion, ultrasonically dispersed in ethanol, centrifuged, dried, tableted, crushed, and sieved to obtain a catalyst.
3. The method for preparing a catalyst according to claim 1, characterized in that In step (1), the mixture is ground for 30 to 40 minutes, dried at 100 to 130°C for 12 to 15 hours, and calcined at 550 to 850°C for more than 2 hours.
4. The method for preparing a catalyst according to claim 1, characterized in that In step (2), the molar ratio of Fe2O3 to CoO is 3 to 4.
5. The method for preparing a catalyst according to claim 1, characterized in that In step (2), alkali is added to adjust the pH.
6. The method for preparing a catalyst according to claim 5, characterized in that: The alkali is one or more of ammonia water, ammonium carbonate and ammonium bicarbonate.
7. The method for preparing a catalyst according to claim 1, characterized in that In step (3), the modifier is preferably one or more of hexadecyltrimethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, vinyltrimethoxysilane, and γ-aminopropyltriethoxysilane.
8. The method for preparing a catalyst according to claim 1, characterized in that In step (4), the molecular sieve is selected from one or more of the molecular sieves SAPO-34, SAPO-18, ZSM-5, and MCM-41.
9. The method for preparing a catalyst according to claim 1, characterized in that In step (4), the mass ratio of the modified active component to the molecular sieve is (1-2):1.
Citation Information
Patent Citations
Method for directly transforming synthesis gas into low-carbon olefin
CN103664436A
Iron-based catalyst for preparing low-carbon alkane as well as preparation method and using method of iron-based catalyst for preparing low-carbon alkane
CN104437524A
Low-CO2-selectivity core-shell catalyst for alkene preparation through CO hydrogenation and preparation method of catalyst
CN107694607A
Compound catalyst for preparing low-carbon olefin from synthetic gas, preparation method of compound catalyst and method for preparing low-carbon olefin from synthetic gas
CN109647503A
Catalyst for preparing low-carbon olefin from synthesis gas and preparation method and use method thereof
CN111266131A